2006
DOI: 10.1007/s11240-006-9079-1
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious regeneration in vitro occurs across a wide spectrum of squash (Cucurbita pepo) genotypes

Abstract: Cucurbita pepo L. (squash, pumpkin) is a highly polymorphic vegetable species of major importance. Our study characterized a spectrum of C. pepo germplasm for the ability to regenerate in vitro by direct organogenesis from cotyledon explants. Cultivars tested included both cultivated subspecies, texana and pepo, and nearly all of their respective cultivar-groups. Direct shoot regeneration occurred in all accessions, and was generally high (56-94%), with a single exception of 22% ('Bolognese'). There was no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 43 publications
6
28
0
8
Order By: Relevance
“…Analysis of ploidy level variation is a useful complementary approach to molecular analysis, which only enables revealing mutations linked to these markers; whilst genomic changes might remain undetected (Jin et al, 2008;Raimondi et al, 2001). Variation in ploidy level after in vitro propagation was detected in many species, e.g., in Titanotrichum oldhamii (Takagi et al, 2011), Cucurbita pepo (Kathiravan et al, 2006), and in Populus x beijingensis (Huang et al, 2015). Thus, development of an efficient system for assessment of in vitro regenerants, making it possible to reveal both molecular and genomic changes, seems to be highly advisable.…”
Section: Issr and Flow Cytomeric Analysesmentioning
confidence: 99%
“…Analysis of ploidy level variation is a useful complementary approach to molecular analysis, which only enables revealing mutations linked to these markers; whilst genomic changes might remain undetected (Jin et al, 2008;Raimondi et al, 2001). Variation in ploidy level after in vitro propagation was detected in many species, e.g., in Titanotrichum oldhamii (Takagi et al, 2011), Cucurbita pepo (Kathiravan et al, 2006), and in Populus x beijingensis (Huang et al, 2015). Thus, development of an efficient system for assessment of in vitro regenerants, making it possible to reveal both molecular and genomic changes, seems to be highly advisable.…”
Section: Issr and Flow Cytomeric Analysesmentioning
confidence: 99%
“…The explant type, plant genotype, seedling age, culture medium, concentration, and a combination of PGRs were the key factors that influenced shoot organogenesis and subsequent plant regeneration (Niederwieser and Staden, 1990;Dabauza and Peña, 2001;Ashrafuzzaman et al, 2009;Prakash and Gurumurthi, 2010). Basal MS medium has been found to be the most effective for adventitious shoot organogenesis in Cucurbitaceous cotyledon explants (Kathiravan et al, 2006;Haque et al, 2008;Zhang et al, 2011). Many reports have indicated that 6-BA alone or in combination with auxin is useful for shoot differentiation (Dong and Jia, 1991;Sarowar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thomas and Sreejesh (2004) have reported that the addition of 0.2 μM NAA with 4 μM 6-benzylaminopurine (BAP) was beneficial for adventitious shoot regeneration in the cotyledon-derived callus of ash gourd. When compared with cucumber (Vasudevan et al, 2004;Vasudevan et al, 2007b), watermelon (Sultana and Bari, 2003;Sultana et al, 2004), melon (Curuk et al, 2002;Muruganantham et al, 2002) and squash (Ananthakrishnan et al, 2003;Kathiravan et al, 2006), chieh-qua also needed a high concentration of 6-BA for shoot induction. Such a high concentration may influence shoot proliferation as well as elongation, and could be one of the reasons for the difficulty of regeneration of chieh-qua.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations